Cover Image, Volume 88, Issue 9. Issue 9 (2nd August 2020) - Mei, Zhe; Treado, John D.; Grigas, Alex T.; Levine, Zachary A.; Regan, Lynne; O'Hern, Corey S.
Abstract : Obverse Cover: The cover image is based on the Original Article Analyses of protein cores reveal fundamental differences between solution and crystal structures by Corey O'Hern et al., https://doi.org/10.1002/prot.25884